Investigación de clamidias en mujeres de la Asociación 22 de Julio de la ciudad de Machala. - Quevedo Gálvez, Christian G. (2007)
The infection for Chamydiasis an illness of sexual transmition that doesn’t present any symptom in many and that it affects the youths mainly. There are three different species: Chlamydia psittaci, Chlamydia pneumoniae and Chlamydia trachomatis. The first two primarily cause respiratory infections, including pneumonia.